PATH-12. TEMOZOLOMIDE-INDUCED HYPERMUTATION IS ASSOCIATED WITH HIGH-GRADE TRANSFORMATION, DISTANT RECURRENCE AND REDUCED SURVIVAL IN INITIALLY LOW GRADE IDH-MUTANT GLIOMAS. (9th November 2020) - Yu, Yao; Villanueva-Meyer, Javier; Chang, Susan; Grimmer, Matthew; Hilz, Stephanie; Solomon, David; Choi, Serah; Wahl, Michael; Mazor, Tali; Hong, Chibo; Shai, Anny; Phillips, Joanna; et al.
Abstract: Temozolomide, a commonly used alkylating agent, can induce somatic hypermutation in gliomas. The prevalence and implications of this phenomenon are not well characterized. Using targeted and whole exome sequencing from a cohort of 82 patients with recurrent IDH -mut LGG, we evaluated the clinical implications of hypermutation. Hypermutation was identified at transformation in 57% of recurrent gliomas exposed to TMZ and occurred for both IDH -mutant astrocytomas (52%) and oligodendrogliomas (64%). Among astrocytomas, receipt of radiotherapy prior to transformation was associated with decreased risk of hypermutation (11% vs 70%, p=0.0052), but this trend was not observed for oligodendrogliomas (78% vs 54%, p=NS). Among hypermutated tumors, 94% were transformed to higher WHO grades. Hypermutation was associated with transformation to higher WHO grade (OR 12.0 95% CI 2.5-115.5, p=0.002) and shorter survival after transformation (HR 2.1, 95% CI 1.1-4.0, p=0.018) compared with non-hypermutated transformed tumors. It remained prognostic (controlling for grade, molecular subtype, age, and prior radiotherapy. Patients with transformation to glioblastoma had poor survival regardless of hypermutation (p=0.78). Multivariate models were validated using an external, independent dataset (Harrel's C=0.72). Strikingly, hypermutated tumors were also associated with development of discontiguous disease after transformation (3-year CI 41% vs 8% p=0.005), including ependymal and leptomeningeal distributions and four cases of spinal dissemination that were not observed in non-hypermutated tumors. These data have significant implications for management of IDH -mut LGG at recurrence.